1962
DOI: 10.1104/pp.37.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Action in Plants as Related to Damage From Photochemical Oxidants

Abstract: A review of the literature indicates that the stomates of leaves must be open for smog damage to occur (3,7,8,9,11). However, there is no direct relationship between degree of opening and extent of injury, nor has it been proven that injury is prevented when the stomates are closed. Moreover, most of the earlier work dealt with the reaction product of ozone and gasoline or ozone and an olefin (8,10,16 Because subsequent assays of plant leaf damage from the oxidant were desired, the rate of apparent photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

1963
1963
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…Dugger, et al, 22 found that stomates in pinto bean opened within 15 to 20 min after being placed in the light, regardless of how long they had been held in the dark. Juhren, et al, 16 showed that a threshold intensity of 4.0 klux was needed to open stomates and found that when intensity was below this level only traces of injury resulted.…”
Section: Discussionmentioning
confidence: 99%
“…Dugger, et al, 22 found that stomates in pinto bean opened within 15 to 20 min after being placed in the light, regardless of how long they had been held in the dark. Juhren, et al, 16 showed that a threshold intensity of 4.0 klux was needed to open stomates and found that when intensity was below this level only traces of injury resulted.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone injury to plants decreased after a 48-hour prefumigation dark period; no injury occurred when the dark period was extended to 72 hours (4,9). Plants grown at 21.5 Klux were less sensitive to ozone than plants grown at 8.5 Klux.…”
mentioning
confidence: 89%
“…
Environmental preconditioning has an important effect on the response of plants to ozone and other oxidants present in photochemical smog (2,4,6,7,9). Ozone injury to plants decreased after a 48-hour prefumigation dark period; no injury occurred when the dark period was extended to 72 hours (4,9).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming specific heats of 1.0 and 0. 4 (4,7) in which complete closure is never indicated. Hygrometric (lata are not conclusive in this matter since it is possible that leakage from the system balances vapor transfer rates below 5c( of that from a free water surface.…”
mentioning
confidence: 99%